2015
DOI: 10.3906/biy-1506-77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod variations and alpha-lipoic acid treatment on melatonin,cortisol, and oxidative stress levels in the blood of rats

Abstract: This study aimed to investigate the effects of frequently changing photoperiods and alpha-lipoic acid treatment on melatonin, cortisol, oxidative markers, and some blood parameters. Eighty-four rats were randomly and equally divided into 7 groups: a control group, 3 prolonged light groups, and 3 prolonged dark groups. The study was completed in 2 stages, with 1-and 4-week periods, respectively. Blood samples were obtained at the end of the first and fourth weeks, and at the end of the dark period for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…On the other hand, AST activity at the hepatic level was modulated by photoperiod exposure, reaching the lowest activity when rats were exposed to the long photoperiod (two-way ANOVA Figure 2b). This finding is in agreement with the data reported by Hardeland et al [30], who demonstrated that mouse liver AST activity is at its maximum during the dark photoperiod; our data also concur with the results reported by Çevik and Aslan [31], who observed that prolonged dark periods enhance the oxidation of nutritional fatty acids and that this oxidation triggers an increase in the AST levels. In contrast, the activity of ALT was not modulated by exposure to the photoperiods.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, AST activity at the hepatic level was modulated by photoperiod exposure, reaching the lowest activity when rats were exposed to the long photoperiod (two-way ANOVA Figure 2b). This finding is in agreement with the data reported by Hardeland et al [30], who demonstrated that mouse liver AST activity is at its maximum during the dark photoperiod; our data also concur with the results reported by Çevik and Aslan [31], who observed that prolonged dark periods enhance the oxidation of nutritional fatty acids and that this oxidation triggers an increase in the AST levels. In contrast, the activity of ALT was not modulated by exposure to the photoperiods.…”
Section: Discussionsupporting
confidence: 94%
“…This finding agrees with the data obtained by Mariné-Casadó et al [4], who previously detected a lack of differences in the ALT values between rats exposed to three photoperiods; similar results confirmed that increasing light photoperiod had no significant effects [32]. It is important to define the status of these biomarkers because ALT and AST are intracellular enzymes released from damaged hepatocytes into the blood following hepatocellular injury [31].…”
Section: Discussionsupporting
confidence: 91%
“…Serum melatonin levels were measured with ELISA method[ 20 ] (Cusabio Biotech, Wuhen, China) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…While melatonin shows a stimulating effect on the gonads in animals, such as sheep, goats, and deer, it shows suppressive properties in animals, such as horses, hamsters, and camels [13]. Melatonin acts as a timer by providing to follow-up the changes in the light/dark ratio of the animal seasonally [14].…”
Section: Introductionmentioning
confidence: 99%